Hubungan Antara Brand Image Dengan Keputusan Pembelian Produk Skincare Pada Remaja Smkn X Padang - Nursaaida Azzahara Mukti; Rina Mariana; Ummil Khairiyah; Rany Fitriany (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The beauty industry in Indonesia has experienced rapid growth alongside the increasing demand for skincare products, particularly among adolescents. Skincare products not only function to maintain skin health but also serve as a means of shaping self-identity, self-confidence, and social acceptance. Adolescents, as a transitional age group, tend to place greater emphasis on physical appearance and are highly influenced by their social environment, social media exposure, and prevailing trends. A positive brand image can enhance adolescents’ trust and confidence in selecting skincare products, often without careful consideration of product suitability for their specific skin needs. This study aimed to examine the relationship between brand image and skincare purchasing decisions among tenth- and eleventh-grade students at SMKN X Padang. A quantitative correlational research design was employed. The sample consisted of 213 respondents selected using a simple random sampling technique. Data were collected through self-administered questionnaires using a Likert-type scale. Data analysis included validity and reliability testing, classical assumption tests, regression analysis, hypothesis testing, and coefficient of determination analysis. The results revealed a positive and highly significant relationship between brand image and skincare purchasing decisions among adolescents at SMKN X Padang. The correlation coefficient was r = .607 with a significance level of p < .001, indicating that the hypothesis was supported. These findings suggest that a more positive brand image is associated with higher purchasing decisions for skincare products among adolescents.